A century and half of hydrogeomorphological disasters in Mainland Portugal - Zêzere, José Luís (2021)
The disaster database lists disastrous floods and landslides registered in mainland Portugal in the period 1865–2015, based on data collected from newspapers. The database includes 1950 hydrogeomorphological disaster cases that caused 1256 deaths, 14,884 evacuated people and 41,977 displaced people. Disastrous floods are clustered in the Lisbon region and the Tagus valley, in the Oporto region and the Douro valley, in the Coimbra region and the Mondego valley and along the Vouga valley. Disastrous landslides are clustered in the Lisbon region and the Douro valley. The period 1935–1969 registered the highest number of disastrous floods and landslides, whereas the last 45 years of the series (1970–2015) do not show any clear temporal trend. However, the 10-year moving average increased at the beginning of the twenty-first century, for floods and landslides, and it is apparent the increasing number of disaster events consisting of several cases, which may result from the increasing occurrence of rainfall extreme events related with climate change. The spatial and temporal trends observed on disastrous floods and landslides reflect the distribution of conditioning factors, the temporal incidence of triggering factors, but also the evolution of the exposure and the vulnerability of people, structures and infrastructures.